Pengaruh Cerita Bergambar terhadap Peningkatan Kemampuan Naratif Anak TK - Danu Eka Prasetyo; Mira Handayani; Jaya Mahendra (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study investigates the effect of picture stories on enhancing the narrative skills of kindergarten children. The background of this research is rooted in the crucial role of narrative ability in early childhood language development, which can be stimulated through engaging learning media. The objective is to examine how the use of picture stories contributes to improvements in children's ability to construct and tell coherent stories. A quasi-experimental method with a pretest-posttest control group design was employed. The participants consisted of 30 kindergarten children, divided into an experimental group receiving picture story interventions and a control group with conventional storytelling. Data were collected through observational rubrics and analyzed using paired and independent sample t-tests. The findings reveal a significant increase in narrative ability in the experimental group compared to the control group. These results suggest that picture stories are effective in fostering young children’s narrative competence. The study implies that early childhood educators should integrate picture stories into learning activities to support children's language development.